Переклад — міст між різними мовними світами? (на підґрунті філософської герменевтики Г. Ґ. Ґадамера) - Березіна, В. (Інститут філософії ім. Г.С. Сковороди НАН України, 2009)
The paper is intended to study the nature of translation as a phenomenological practice of understanding. The purpose is to explore Gadamer's way of speaking about translation whereby translation practice as interpretation can be seen as ontological event. The author focuses mainly on such central themes regarding translation practice: (a) phenomenology of linguistic world, (b) boundaries of language, and (c) inadequacy of translation. For each of these themes, an instrumental theory of language is compared with non instrumental one drawn from a hermeneutic approach. There is discussed Gadamer's difference between language and linguistics to explain the coexistence of plurality of languages and unity of understanding that allows possibility of translation. The paper also analyses important notion of rituality that philosopher offers to show difference between human language and animal communication. Finally, the author explores Gadamer's metaphor of a bridge between linguistic worlds that shows possibilities and limitations of translation practice. Translation is not a simple act of word-to-word reproduction or on the contrary the creation of a new text. Rather it is the transfer of the sense of what is said with one language in order to say it with another language.